2012
DOI: 10.1002/emmm.201201486
|View full text |Cite
|
Sign up to set email alerts
|

WLS inhibits melanoma cell proliferation through the β‐catenin signalling pathway and induces spontaneous metastasis

Abstract: Elevated levels of nuclear β-catenin are associated with higher rates of survival in patients with melanoma, raising questions as to how ß-catenin is regulated in this context. In the present study, we investigated the formal possibility that the secretion of WNT ligands that stabilize ß-catenin may be regulated in melanoma and thus contributes to differences in ß-catenin levels. We find that WLS, a conserved transmembrane protein necessary for WNT secretion, is decreased in both melanoma cell lines and in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
2

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 46 publications
0
26
2
Order By: Relevance
“…In order to gain further insight into the observed role for WNT5A in promoting the viability of both naive and BRAFi-resistant melanomas, we then focused on identifying signaling pathways acting downstream of WNT5A in melanoma. We and others have recently shown that activation of WNT/β-catenin-dependent signaling with WNT3A can inhibit the proliferation of melanoma cells in vitro and in vivo (24,30,31). Since several studies indicate that WNT5A can act as a negative regulator of WNT/β-catenin-dependent transcription (32,33), these data suggest that WNT5A might promote melanoma growth by inhibiting WNT/β-catenin signaling.…”
Section: Figurementioning
confidence: 80%
“…In order to gain further insight into the observed role for WNT5A in promoting the viability of both naive and BRAFi-resistant melanomas, we then focused on identifying signaling pathways acting downstream of WNT5A in melanoma. We and others have recently shown that activation of WNT/β-catenin-dependent signaling with WNT3A can inhibit the proliferation of melanoma cells in vitro and in vivo (24,30,31). Since several studies indicate that WNT5A can act as a negative regulator of WNT/β-catenin-dependent transcription (32,33), these data suggest that WNT5A might promote melanoma growth by inhibiting WNT/β-catenin signaling.…”
Section: Figurementioning
confidence: 80%
“…To confirm the role of Porcn function in Evi regulation without manipulating Wnt expression, we monitored Evi in the colon cancer cell line HCT116, that depends on Wnt secretion (Voloshanenko et al , 2013) and in the melanoma cell line A375, that expresses Wnt5A and Wnt10B endogenously (Yang et al , 2012). LGK974 treatment of HCT116 and A375 cells reduced Evi protein levels in a time‐dependent manner and depleted Evi below the detection limit after 24–48 h (Fig 2E) without reducing Evi mRNA levels (Fig EV2C and D).…”
Section: Resultsmentioning
confidence: 99%
“…In human, both WLS and SFRP2 have been implicated in various cancers. In particular, concomitant epigenetic silencing of SOX1 and SFRPs was reported in hepatocellular carcinoma [47][48][49][50]. It would be interesting to test whether SOX2 contributes to tumor development through transcriptionally controlling WLS and SFRP2 expression.…”
Section: Discussionmentioning
confidence: 97%